Portal Vein Thrombosis in the Setting of Newly Diagnosed Cushing's Syndrome - Alexandria D. McDow MD; Anju Gurung MD; Rama Poola MD; Carmel Fratianni MD; Marc Garfinkel MD; Michael G. Jakoby MD/MA (SAGE Publishing, 2017)
The hallmark manifestations of Cushing's syndrome (CS) are well known, but hypercoagulability is perhaps least recognized. Patients with CS are at increased risk of both spontaneous and postoperative thromboembolism, with the significant majority of events occurring in the lower extremity and pulmonary venous circulations. We present a case of portal vein thrombosis (PVT) occurring in the setting of newly diagnosed CS due to a left adrenal adenoma. Factor VIII activity was approximately 2.5-fold elevated, a known mechanism by which hypercortisolemia predisposes to venous thrombosis. Acute abdominal pain and fever responded well to unfractionated heparin and parenteral antibiotics, and CS was eventually cured by left adrenalectomy. No thromboembolic events have occurred since surgery. PVT is uncommon and usually occurs as a complication of primary or secondary hepatobiliary malignancies and cirrhosis. To the best of our knowledge, this is just the second reported case of PVT due to CS and the first published in the English language literature.